POHON CITA-CITA SEBAGAI MEDIA EDUKATIF DALAM MENINGKATKAN SEMANGAT BELAJAR SISWA SEKOLAH DASAR - Elysa Rohayani Hsb, Laili Habibah Pasaribu, Rizki Syahputra, Lily Rohanita Hasibuan, Asriani Hasibua (PT.JNDI, JURNAL BIMA, 2026)
Community Service Activities are a form of community action that has a positive impact on the community through activities that benefit the surrounding environment. One example is providing educational programs such as the Dream Tree in elementary schools, which aims to foster learning motivation and encourage students to plan their dreams from an early age. This community service is carried out using a participatory method, where students write their dreams on leaf-shaped paper which is then attached to the dream tree. This activity received a positive response from students and teachers because it was able to create a pleasant learning atmosphere, increase students' self-confidence, and instill the importance of having a life goal. The results of this community service activity show that the Dream Tree is effective as an educational medium in fostering a spirit of learning and building optimism in elementary school students.